Vitamin D concentration effect in health care and sport performance - Lora Georgieva; Katarzyna Żołądkiewicz; Walery Żukow (Kazimierz Wielki University, 2018)
The molecular structure of Vitamin D is closely allied to that of classical steroids such as cholesterol. Technically Vitamin D is a seco-steroid hormone. Vitamin D3 (cholecalciferol) is normally produced by exposure to sunlight of the precursor (7-dehydrocholesterol), present in the skin. Vitamin D supplementation vary between 200 IU to 1000 IU. Serum levels of 25(OH)D are generally consider as a indicator of Vitamin D status. Vitamin D plays an essential role in healthcare, related not only with developing and maintaining a healthy skeleton. Its adequate supplementation reduce even the risk of caries and oral infections. Furthermore Vitamin D as a steroid hormone, modulates many gene transcription and has anti-inflammatory and cardiovascular protective effect. Uncertainly low serum levels of 25(OH)D are associated with misbalance in lipid profile and dyslipidemia, sacropenia and muscle weakness. Its insufficiency is also a risk factor for enhanced reception of pain, risk of type 2 diabetes, and often falls occurrences. Adequate Vitamin D status is protective against musculoskeletal disorders, infection disease, depression, diabetes mellitus, autoimmune diseases and neurocognitive dysfunctions. In sport activities and athletic population adequate serum levels of 25(OH)D increase muscle strength, and physical performance, and should be monitored.